Toughening mechanisms in V-Si-N coatings. (1st November 2021) - Ge, F.F.; Sen, H.S.; Daghbouj, N.; Callisti, M.; Feng, Y.J.; Li, B.S.; Zhu, P.; Li, P.; Meng, F.P.; Polcar, T.; Huang, F.
Graphical abstract: Highlights: Super hardness and toughness of VSiN are achieved with Si content at 5.5 at.% Si. With Si content, highly textured columnar grains, refined columnar grains, nanocomposite structure are formed. DFT revealed that the ternary VSiN coatings become more ductile as the calculated Cauchy pressures (PC ) raise, while the Pugh's ratios (G/B) decrease. Transfer of electrons to the Si-N bond from the neighboring V-N bonds causes Friedel oscillations and multiplication of the slip system. Abstract: Microstructural evolution and deformation mechanisms of magnetron sputtered V-Si-N coatings with various Si contents are investigated by transmission electron microscopy, X-ray absorption spectroscopy, and ab initio calculations. A small amount of Si atoms was dissolved into the cubic VN lattice, locally reducing the neighboring V-N p-d hybridization near the Si site. The Si content was found to impact the architecture of coating significantly. With increasing Si content, the microstructure evolved through three different architectures: (i) highly textured columnar grains, (ii) refined columnar grains, and (iii) nanocomposite structures where elongated grains were bounded by vein-like boundaries. Enhanced damage tolerance was observed in the nanocomposite structure, where multiple toughening mechanisms become active. Ab initio calculations revealed that the incorporation of Si monolayer in the (1 1 1)-oriented VN resulted in the formation of weaker Si-N bonds compared to V-N bonds, which allowed a selective response to strain and shear deformations by assisting the activation of the slip systems.